Analisis Rancangan Trainer Kombinasi PV Tipe Polycrystalline dan Monocrystalline pada EBT - Sebayang, Youstra; Satria, Habib; Azmi, Fadhillah (Universitas Medan Area, 2024)
Trainer is a medium object similar to real objects that facilitates learning. Solar energy is renewable energy.Each type of PV has its own advantages and disadvantages. In this regard, the design of a solar panel trainer, a combination of pollycrystalline and monocrystalline PV type in NRE, aims to be a learning medium for Newand Renewable Energy (EBT). Solar panels of polycrystalline and monocrystalline types have different characteristics, performance, and efficiency. To get the results of the data so that it can be analyzed, the trainer is designed using a DC Wattmeter, Solar Charge Controller, and Battery. The experiment was conducted on July 17, 2022 and in this trainer can be seen the average efficiency on polycrystalline solar panels of 12.01%, monocrystalline solar panels of 6.11%, and parallel polycrystalline and monocrystallinesolar panels of 4.20%.